PELATIHAN PENGENDALIAN TERPADU HAMA TOMAT DAN TANAMAN SELA KOPI TEPAT GUNA DI DESA MUARA SALADI, KEC. ULU PUNGKUT, KAB.MADINA, SUMATERA UTARA - Ameilia Zuliyanti Siregar; Darma Bakti; Irsal Irsal (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2020)
Community service activities of the Non PNBP Assisted Village Program in Increasing Farmers' Income through Integrated Agriculture in Muara Saladi Village, Ulu Pungkut District, Madina Regency, North of Sumatra. Implemented from May 2020 to October 2020. The approach method used was through potential / problem surveys, socialization, focus group discussions (FDG), training, mentoring activities and evaluation monitoring. Socialization and training were carried out, including Introduction to Soil Types and Land Suitability for Tomato Planting, Knowledge of Cultivation and Integrated Pest Management for Tomato and Vegetable Plants as well as planting of maga oranges and sweet fragrant manga as protective crops on coffee plants. The use of yellow glue traps (YST), Sweep nets and the manufacture of environmentally friendly vegetable pesticides from garlic, papaya and sour sop leaves, through training sessions and practice in tomato plantations is an effective way to manage integrated pest friendly environment. The use of vegetable pesticides in horticultural crops to control pests and diseases. Integrated pests and diseases increase the productivity of vegetables in an appropriate manner so that it supports increased income and welfare of horticultural farmers in Madina.